A Re-examination of Online Marketing Strategies for Graduate Recruitment in the Insurance Industry - Rana, Zain (2010)
"Cynics sometimes refer to the insurance industry as boring, old-fashioned and bureaucratic. What can Zurich do to challenge such misconceptions and better market themselves to potential graduate applicants?”